Factors Affecting Brand Loyalty in the Branded Cafe Industry in the Jabodetabek Area - Ivander, Hans Fernando; Sidharta, Yusuf (Budapest International Research and Critics University, 2021)
The purpose of this study was to analyze the positive effect of perceived communication consistency on brand trust, affective brand commitment, and brand loyalty. This study also analyzed the positive effect of brand trust on affective brand commitment and brand loyalty, in addition, to analyze the positive effect of affective brand commitment on brand loyalty. Data were collected by an online questionnaire that had been shared on social media, with the target to Jabodetabek residents that like to go to a branded cafe and following the said branded cafe media social account. 278 samples were collected using purposive sampling and then analyzed using the Partial Least Squares - Structural Equation Modelling (PLS-SEM) approach, which was processed by SmartPLS software. The result of this study showed that almost all of the hypotheses were accepted (i.e.: having positive effects); however, perceived communication consistency was found not to have a positive effect on affective brand commitment.